UJI DAYA TERIMA NUGGET PANGGANG DENGAN SUBTITUSI JAMUR TIRAM, WORTEL, DAN TEPUNG JAGUNG SEBAGAI PRODUK SNACK SEHAT SUMBER SERAT - Bifadhlika Alya; Imelda Telisa; Terati Terati (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2023)
Background: Indonesia has a high prevalence of obesity. One of the efforts that can be done to overcome the problem of obesity is through an innovative approach to products rich in healthy dietary fiber. The types of food that can be increased in availability are oyster mushrooms, carrots, and corn flour. Methods: This research is an experimental study using a non-factorial Completely Randomized Design (CRD) with 3 corn flour substitution formulations F1 (50 g), F2 (60 g), F3 (70 g). Organoleptic test research subjects were 30 panelists. Results: Based on the results of organoleptic tests (color, aroma, taste, and texture) showed that the acceptance of baked nuggets with oyster mushroom, carrot and corn flour substitutions was the most preferred F1 with 159.54 kcal energy, 5.25% protein, 2.22 fat. %, 29.64% carbohydrates, and 11.59% dietary fiber in 100 grams. Fried test showed a relationship between color, aroma, taste, and texture. Conclusion: Based on the results of the research, it can be concluded that baked nuggets with the substitution of oyster mushrooms, carrots and corn flour can be used as an alternative source of fiber snacks. To supply the needs of energy, protein, fat, carbohydrates and fiber in snacks, teenagers can consume 3 pieces of baked nuggets with substitutions of oyster mushrooms, carrots and corn flour, which is 120 grams a day.